PERBANDINGAN KELAINAN HEMATOLOGI ANTARA PASIEN INFEKSI DENGUE PRIMER DAN SEKUNDER DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG: Comparison of Hematological Abnormalities Between Primary and Secondary Dengue Infection Patient at Regional General Hospital Dr. H. Abdul Moeloek, Lampung - Hidayat; Triwahyuni, Tusy; Zulfian, Zulfian; Iskandar, Fryiska Fauziah (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2021)
Dengue Hemorrhagic Fever is an endemic disease caused by the dengue virus. Dengue infection can be classified into primary and secondary dengue infection. The routine blood test is usually do for screening in dengue fever patient by checking hemoglobin, hematocrit, platelet count, leukosit, MCV, MCH, MCHC. This Study aimed to determine the comparison of hematological abnormalities in patients with primary and secondary dengue infection. The research was analytic observational method with cross-sectional research design. The number of samples in this study were 39 patients. Data were analyzed by independent T test and Mann Whitney test. The results showed that there were 5 patients infected with primary dengue (12.8%) and 34 people (87.2%) who were infected with secondary dengue. In primary dengue infection, the mean hemoglobin level was 14.9gr/dL, the mean number of leukocytes was 4.560/µL, the mean hematocrit was 44.80%, the median platelet count was 25,000 / µL, the mean MCV was 85 fL, the median MCH was 29 pg, the median MCHC is 33 gr/dL. In secondary dengue infection, the mean hemoglobin level was 14.0 gr/dL, the mean number of leukocytes was 4.700/µL. The mean hematocrit was 41.88%, the median platelet count was 38.500 / µL, the mean MCV was 85.18 fL, the median MCH was 28 pg, the median MCHC was 33 gr/dL. The results of statistical tests showed that there was no difference in hematological abnormalities between patients with primary dengue infection and secondary dengue infection. Haematological studies such as hematocrit, additional sample size and cohort study methods are required in further research.